Design and Implementation of Green Human Resource Management (Green HRM) in SMEs Palembang City - Setiawan, Heri; Susanto, Sani; Rinamurti, Micheline; Alfian, Achmad (Jurnal Ekuisci, 2025)
The purpose of this research is to explore the design and implementation process of the concept of Green HRM. The informants in this study are owners/management representatives of SMEs, Field assistant lecturers (DPL), and MBKM students of the MBKM Programme. The research method is a qualitative case study approach; data collection is carried out by in-depth observation of SMEs participating in the Batch 1 LLDikti Region 2 Independent SMEs Programme in Palembang City. This research data analysis uses interactive data analysis. The results showed that SMEs have not perfectly and explicitly designed and implemented Green HRM. However, SMEs have attempted to build green worker behavior in aspects of recruitment and selection, worker training and development, compensation and benefits, organizational culture, and performance management. Some of the benefits obtained are workers are more regular and live healthier lives, the name of SMEs in the general public, skilled and committed workers, reduced negative impacts that occur, reduced waste, and even recycling so as to reduce costs, improve the economic welfare of the community, ensure the sustainability of SMEs and natural resources, increase performance and productivity of SMEs, build a green work environment, form a green culture and green lifestyle.